A Life History Theory of Father Absence and Menarche: A Meta-Analysis. (1st April 2014) - Webster, Gregory D.; Graber, Julia A.; Gesselman, Amanda N.; Crosier, Benjamin S.; Schember, Tatiana Orozco
Is the absence of biological fathers related to their daughters' earlier age at menarche? Drawing on evolutionary psychology and life history theory, prior research has suggested such a relationship (Belsky, Steinberg, and Draper, 1991 ;Draper and Harpending, 1982 ;Ellis, 2004 ). Although qualitative reviews have shown narrative support for this relationship (Allison and Hyde, 2013 ;Ellis, 2004 ;Kim, Smith, and Palermiti, 1997 ;Susman and Dorn, 2009 ), no quantitative review exists to provide empirical support for this relationship or to explain mixed results. Thus, we conducted a random-effects meta-analysis of correlations (Card, 2012 ) on father absence and daughter menarcheal age ( k = 33; N = 70, 403). The weighted mean correlation was .14, 95% CI [.09, .19], suggesting that father absence was significantly related to earlier menarche; effect sizes were heterogeneous. Egger's regression (Egger, Smith, Schneider, and Minder, 1997 ) showed no evidence of publication bias (file-drawer effect; r = .34, p = .052). Outcome measure differences (menarcheal age vs. menarcheal age embedded in a multi-item pubertal timing scale) did not moderate effect sizes. Study year effects (Schooler, 2011 ) were also non-significant. Our findings support one aspect of the life history model and provide groundwork for subsequent examination of other pathways in the model.